Self-cleaning and anti-adhesion rubber and preparation method thereof

By adding specific components and processes to the rubber, a hydrophobic surface with self-cleaning and anti-adhesion properties is prepared, which solves the problem of accumulation of rubber tracks in harsh environments, and achieves efficient cleaning and anti-fouling performance of rubber surfaces and prolongs use. Lifespan and reduce vehicle power consumption.

CN116376128BActive Publication Date: 2024-12-27BAODING SANYUAN RUBBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310491047.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-04
Publication Date
2024-12-27
Estimated Expiration
2043-05-04

AI Technical Summary

Technical Problem

Rubber tracks are prone to accumulation of mud chips and sand in harsh environments, resulting in component movements affected, service life decreased and vehicle power consumption increased. The existing superhydrophobic surface preparation methods are complex, costly and poor stability.

Method used

Using natural rubber, nano zinc oxide, organically modified silicone, activated alumina, fluoropolymer and lubricant, rubber with self-cleaning and anti-adhesion properties is prepared through specific kneading and vulcanization processes. , simulate the hydrophobic surface effect of lotus leaves.

Benefits of technology

The rubber surface is self-cleaning and anti-adhesion effect is achieved, with a contact angle greater than 90°. It still maintains excellent hydrophobic performance after 24 months of outdoor exposure, effectively avoiding contaminants adhesion, extending service life and reducing vehicle power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116376128B_ABST
    Figure CN116376128B_ABST
Patent Text Reader

Abstract

The present invention discloses a self-cleaning and anti-adhesion rubber and a preparation method thereof, and belongs to the technical field of rubber rubber. The self-cleaning and anti-adhesion rubber of the present invention comprises the following components in parts by weight: 90 to 110 parts of natural rubber, 4 to 6 parts of nano zinc oxide, 1 to 3 parts of stearic acid, 3 to 5 parts of antioxidant, 1 to 3 parts of paraffin, 45 to 55 parts of carbon black, 4 to 6 parts of aromatic oil, 1.0 to 1.5 parts of accelerator, 2 to 3 parts of sulfur, 2 to 10 parts of organic modified silicone, 3 to 4 parts of activated alumina, 4 to 6 parts of fluorine-containing polymer and 2 to 3 parts of lubricant. The self-cleaning and anti-adhesion rubber of the present invention has an excellent self-cleaning effect and can effectively prevent pollutants from adhering to the rubber surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber compounds, in particular to a self-cleaning and anti-adhesion rubber and a preparation method thereof. Background Art

[0002] Rubber tracks are often used in harsh environments such as muddy and muddy areas. It is inevitable that mud and sand will be drawn into the system and accumulate. These accumulated mud and sand will affect the mutual movement of the rubber track components, thus reducing the service life of the rubber track and its components. In addition, the accumulation of mud and sand will also increase the weight of the rubber track walking system, resulting in increased power consumption of the vehicle.

[0003] The self-cleaning effect possessed by the hydrophobic surface similar to lotus leaves has become a hot topic of research in recent years due to its wide use value. This hydrophobic surface has a special wettability, and water droplets present good geometric morphology on its surface, which cannot be wetted, and when the water droplets do not wet, by free rolling, solid surface impurities such as dust can be taken away, achieving the effect of self-cleaning. At present, the methods for preparing super-hydrophobic surfaces are too numerous to mention, and commonly used ones include template method, etching method, deposition method, electrochemical method, phase separation method, self-assembly method, particle filling method, etc. However, these methods have some inherent defects, such as cumbersome and complicated production process, long production cycle, and high cost; and the preparation matrix is ​​mostly selected from hard substrates such as metals and plastics, and the prepared super-hydrophobic products have poor stability and wear resistance. Therefore, it is important to find a simple, low-cost, and highly stable process method for the products produced to prepare super-hydrophobic surfaces, which has important theoretical and practical significance. Summary of the invention

[0004] The purpose of the present invention is to provide a self-cleaning, anti-adhesion rubber and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a self-cleaning, anti-adhesion rubber, comprising the following components in parts by weight: 90 to 110 parts of natural rubber, 4 to 6 parts of nano zinc oxide, 1 to 3 parts of stearic acid, 3 to 5 parts of antioxidant, 1 to 3 parts of paraffin, 45 to 55 parts of carbon black, 4 to 6 parts of aromatic oil, 1.0 to 1.5 parts of accelerator, 2 to 3 parts of sulfur and 2 to 10 parts of organic modified silicone.

[0007] Adding organic modified silicone (Silicone aid 1330, organic modified silicone containing vinyl reactive functional groups) to rubber can reduce the surface energy of the rubber, thereby improving the self-cleaning and anti-adhesion properties of the rubber.

[0008] Since organic modified silicone has many active functional groups, it has good affinity with rubber and can be mixed into rubber in a certain proportion to produce a self-cleaning and anti-adhesion effect similar to the hydrophobic surface of lotus leaves. This hydrophobic surface has a special wettability, and water droplets present a good geometric morphology on its surface and cannot infiltrate it. Moreover, while the water droplets do not infiltrate it, they can carry away dust and other solid surface impurities through their own rolling, achieving the effect of self-cleaning and anti-adhesion.

[0009] Furthermore, the self-cleaning and anti-adhesive rubber further comprises the following components in parts by weight: 3 to 4 parts of activated alumina, 4 to 6 parts of fluorine-containing polymer and 2 to 3 parts of lubricant.

[0010] Activated alumina and the vinyl active groups in organic modified silicone can form a dense structural layer to avoid the increasingly serious problem of rubber vertical flow pollution caused by the entry and retention of pollutants.

[0011] Fluoropolymers can further reduce the surface energy of rubber, and fluorine-containing polymers can work together with organic modified silicone and activated alumina to enhance the self-cleaning and anti-adhesion effects of rubber.

[0012] Lubricants can improve the dispersibility of nano zinc oxide and enhance the anti-cracking performance of rubber.

[0013] Furthermore, the lubricant is castor oil polyoxyethylene ether oleate.

[0014] Furthermore, the preparation method of the fluorine-containing polymer specifically comprises:

[0015] A. Mix β-cyclodextrin and potassium hydroxide solution evenly and stir to react, then drop epichlorohydrin, and heat to react after the dropwise addition is completed, precipitate, and obtain an intermediate product;

[0016] B. Dispersing the intermediate product in water, adding potassium persulfate solution under a protective atmosphere, stirring to react, then sequentially adding acrylamide solution and perfluoroalkenyloxybenzenesulfonyl chloride, heating to react, and obtaining the fluorine-containing polymer.

[0017] Furthermore, in step A, the concentration of the potassium hydroxide solution is 10-15wt.%; the mass / volume ratio of the β-cyclodextrin and the potassium hydroxide solution is 1g:8-10mL; the stirring reaction time is 45-55min; the mass / volume ratio of the β-cyclodextrin and epichlorohydrin is 1:0.1-0.2mL; the heating reaction temperature is 55-60°C, and the time is 8-9h.

[0018] Furthermore, in step B, the mass / volume ratio of the intermediate product and water is 1 mg:4-5 mL; the concentration of the potassium persulfate solution is 0.5 wt.%; the mass ratio of the intermediate product and the potassium persulfate in the potassium persulfate solution is 1:2; the concentration of the acrylamide solution is 15-20 wt.%; the temperature of the heating reaction is 60-65° C., and the time is 8-10 h.

[0019] Furthermore, the particle size of the nano zinc oxide is 10-30 nm; the antioxidant is composed of antioxidant RD and antioxidant 4010 in a mass ratio of 1:1.

[0020] Furthermore, the carbon black is carbon black N330; and the accelerator is accelerator CZ.

[0021] Technical solution 2 of the present invention: A method for preparing the above-mentioned self-cleaning and anti-adhesion rubber comprises the following steps:

[0022] The raw materials are mixed according to their mass fractions and then kneaded. After the kneading is completed, thin-pass and vulcanization are performed to obtain the self-cleaning and anti-adhesion rubber.

[0023] The mixing is specifically as follows: controlling the temperature of the internal mixer to be about 55-65° C., the rotation speed to be 25-35 r / min, mixing for 4-6 minutes, and finally controlling the temperature of the internal mixer to be 85-95° C., discharging the rubber and obtaining the mixed rubber.

[0024] Specifically, the mixed rubber is moved to an open mixing mill for thin-pass kneading, the roller distance of the open mixing mill is adjusted to 1 mm, the roller temperature is controlled to be 50-55°C, and plasticization is performed. The mixed rubber is thin-passed 4-6 times, and finally the roller distance is increased to 2.5 mm for thin-pass kneading, and the mixed rubber is allowed to stand for 8-16 hours to obtain plasticized rubber.

[0025] Vulcanization is as follows: the plasticized rubber is heated at a temperature of 140-150°C and a pressure of 200-220 kgf / cm 2 Under the conditions of , vulcanization is carried out for 15 to 25 minutes to obtain a self-cleaning and anti-adhesion rubber.

[0026] Technical solution three of the present invention: A method for preparing the above-mentioned self-cleaning and anti-adhesion rubber, comprising the following steps:

[0027] Weigh each raw material by mass, mix natural rubber, stearic acid, antioxidant, paraffin, carbon black, aromatic oil, accelerator and sulfur evenly and knead them once, then add nano zinc oxide, organic modified silicone, activated alumina, fluorine-containing polymer and lubricant for secondary kneading, and finally thin pass and vulcanize to obtain the self-cleaning and anti-adhesion rubber.

[0028] The present invention discloses the following technical effects:

[0029] (1) The self-cleaning and anti-adhesion rubber of the present invention has an excellent self-cleaning effect and can effectively prevent pollutants from adhering to the rubber surface.

[0030] (2) The self-cleaning and anti-adhesive rubber of the present invention has a hydrophobic surface similar to that of a lotus leaf, with a contact angle greater than 90°, and after being exposed outdoors for 24 months, it still has a large contact angle and excellent hydrophobic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 This is a schematic structural diagram of the anti-adhesion test workbench used in the present invention. DETAILED DESCRIPTION

[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0034] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0038] The “parts” described in the following examples are all “parts by mass”.

[0039] The particle size of the nano zinc oxide used in the following examples and comparative examples of the present invention is 10 to 30 nm.

[0040] The organic modified silicone (Silicone aid 1330, an organic modified silicone containing vinyl reactive functional groups) used in the following examples and comparative examples of the present invention was purchased from Shanghai Yinghe Chemical Co., Ltd.

[0041] Example 1

[0042] A method for preparing self-cleaning and anti-adhesion rubber:

[0043] (1) A self-cleaning, anti-adhesive rubber, comprising the following components in parts by weight: 110 parts of natural rubber, 4 parts of nano zinc oxide, 3 parts of stearic acid, 2.5 parts of antioxidant RD, 2.5 parts of antioxidant 4010, 1 part of paraffin, 45 parts of carbon black N330, 6 parts of aromatic oil, 1.0 part of accelerator CZ, 3 parts of sulfur and 2 parts of organic modified silicone.

[0044] (2) Preparation method

[0045] A. Mixing: Add natural rubber, antioxidant RD, antioxidant 4010, paraffin, carbon black N330, aromatic oil, accelerator CZ, sulfur, nano zinc oxide, stearic acid and organic modified silicone into an internal mixer in sequence, then control the temperature of the internal mixer to about 65°C and the speed to 25r / min, mix for 6 minutes, and finally control the temperature of the internal mixer to 85°C, discharge the rubber and obtain the mixed rubber.

[0046] B. Thin pass: Move the mixed rubber to an open mixing mill and thinly pass it for kneading. Adjust the roller distance of the open mixing mill to 1mm, control the roller temperature to 50℃, and perform plasticizing. Thinly pass the mixed rubber for 6 times. Finally, increase the roller distance to 2.5mm and let it stand for 16 hours to obtain plasticized rubber.

[0047] C. Vulcanization: Put the plasticized rubber into a mold with a length, width and thickness of 100mm and 2mm, and then heat it at a temperature of 150℃ and a pressure of 220kgf / cm 2 Under the conditions of , vulcanization was carried out for 15 min to obtain a self-cleaning and anti-adhesion rubber.

[0048] Example 2

[0049] A method for preparing self-cleaning and anti-adhesion rubber:

[0050] (1) A self-cleaning, anti-adhesive rubber, comprising the following components in parts by weight: 90 parts of natural rubber, 6 parts of nano zinc oxide, 1 part of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4010, 3 parts of paraffin, 55 parts of carbon black, 4 parts of aromatic oil, 1.5 parts of accelerator, 2 parts of sulfur and 2 parts of organic modified silicone.

[0051] (2) Preparation method

[0052] A. Add natural rubber, antioxidant RD, antioxidant 4010, paraffin, carbon black N330, aromatic oil, accelerator CZ, sulfur, nano zinc oxide, stearic acid and organic modified silicone into the internal mixer in sequence, then control the temperature of the internal mixer to about 55°C and the speed to 35r / min, mix for 4min, and finally control the temperature of the internal mixer to 95°C, discharge the rubber and obtain the mixed rubber.

[0053] B. Thin pass: Move the mixed rubber to an open mixing mill and thinly pass it for kneading. Adjust the roller distance of the open mixing mill to 1mm, control the roller temperature to 55℃, and perform plasticizing. Thinly pass the mixed rubber for 4 times. Finally, reduce the roller distance to 2.5mm and let it stand for 8h to obtain plasticized rubber.

[0054] C. Vulcanization: Put the plasticized rubber into a mold with a length, width and thickness of 100mm and 2mm, and then vulcanize it at a temperature of 140℃ and a pressure of 200kgf / cm 2 Under the conditions of 25min, a self-cleaning and anti-adhesive rubber was obtained.

[0055] Example 3

[0056] A method for preparing self-cleaning and anti-adhesion rubber:

[0057] (1) A self-cleaning and anti-adhesive rubber, comprising the following components in parts by weight: 100 parts of natural rubber, 5 parts of nano zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant RD, 2 parts of antioxidant 4010, 1-3 parts of paraffin, 50 parts of carbon black N330, 5 parts of aromatic oil, 1.2 parts of accelerator CZ, 2.5 parts of sulfur and 2 parts of organic modified silicone.

[0058] (2) Preparation method

[0059] A. Add natural rubber, antioxidant RD, antioxidant 4010, paraffin, carbon black N330, aromatic oil, accelerator CZ, sulfur, nano zinc oxide, stearic acid and organic modified silicone into the internal mixer in sequence, then control the temperature of the internal mixer to about 60℃ and the speed to 30r / min, mix for 5min, and finally control the temperature of the internal mixer to 90℃, discharge the rubber and obtain the mixed rubber.

[0060] B. Thin pass: Move the mixed rubber to an open mixing mill and thinly pass it for kneading. Adjust the roller distance of the open mixing mill to 1mm, control the roller temperature to 52℃, and perform plasticizing. Thinly pass the mixed rubber for 5 times, and finally thicken the rubber by reducing the roller distance to 2.5mm and let it stand for 12 hours to obtain plasticized rubber.

[0061] C. Vulcanization: Put the plasticized rubber into a mold with a length, width and thickness of 100mm and 2mm, and then vulcanize it at a temperature of 145℃ and a pressure of 210kgf / cm 2 Under the conditions of , vulcanization was performed for 20 min to obtain a self-cleaning and anti-adhesion rubber.

[0062] Example 4

[0063] Same as Example 3, except that the amount of the organic modified silicone is adjusted to 4 parts.

[0064] Example 5

[0065] Same as Example 3, except that the amount of the organic modified silicone is adjusted to 6 parts.

[0066] Example 6

[0067] Same as Example 3, except that the amount of the organic modified silicone is adjusted to 8 parts.

[0068] Example 7

[0069] Same as Example 3, except that the amount of the organic modified silicone is adjusted to 10 parts.

[0070] Example 8

[0071] Same as Example 3, except that the amount of the organic modified silicone is adjusted to 12 parts.

[0072] Example 9

[0073] A method for preparing self-cleaning and anti-adhesion rubber:

[0074] (1) A self-cleaning and anti-adhesive rubber, comprising the following components in parts by weight: 90 parts of natural rubber, 6 parts of nano zinc oxide, 1 part of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4010, 3 parts of paraffin, 55 parts of carbon black, 4 parts of aromatic oil, 1.5 parts of accelerator, 2 parts of sulfur, 10 parts of organic modified silicone, 3.5 parts of activated alumina, 5 parts of fluorine-containing polymer and 3 parts of lubricant (castor oil polyoxyethylene ether oleate).

[0075] The preparation method of the fluorine-containing polymer is:

[0076] A. Mix 1g of β-cyclodextrin and 9mL of 12wt.% potassium hydroxide solution, stir and react for 50min, then slowly drop 0.2mL of epichlorohydrin, heat and react after the addition is complete (temperature is 58°C, time is 9h, stirring speed is 300r / min), add acetone to precipitate after the reaction is complete, wash the precipitate with 50vol.% ethanol aqueous solution to obtain an intermediate product.

[0077] B. Disperse 10 mg of the intermediate product in 45 mL of water, add 4 g of a 0.5 wt.% potassium persulfate solution under a nitrogen atmosphere, and stir the reaction at 40°C for 30 min. Then, add 10 g of an 18 wt.% acrylamide solution and 200 mg of perfluoroalkenyloxybenzenesulfonyl chloride to the reaction system, and react at 65°C for 10 h. After the reaction, dry the mixture to obtain a fluorine-containing polymer.

[0078] (2) Preparation method

[0079] A. Add natural rubber, antioxidant RD, antioxidant 4010, paraffin, carbon black N330, aromatic oil, accelerator CZ, sulfur, and stearic acid to the internal mixer in sequence, then control the temperature of the internal mixer to about 60°C and the speed to 30r / min, and mix for 3min. Then add nano zinc oxide, organic modified silicone, activated alumina, fluorine-containing polymer, and lubricant, control the temperature of the internal mixer to about 65°C and the speed to 35r / min, and mix for 6min. Finally, control the temperature of the internal mixer to 90°C, discharge the rubber, and obtain the mixed rubber.

[0080] B. Thin pass: Move the mixed rubber to an open mixing mill and thinly pass it for kneading. Adjust the roller distance of the open mixing mill to 1mm, control the roller temperature to 52℃, and perform plasticizing. Thinly pass the mixed rubber for 5 times, and finally thicken the rubber by reducing the roller distance to 2.5mm and let it stand for 12 hours to obtain plasticized rubber.

[0081] C. Vulcanization: Put the plasticized rubber into a mold with a length, width and thickness of 100mm and 2mm, and then vulcanize it at a temperature of 145℃ and a pressure of 210kgf / cm 2 Under the conditions of , vulcanization was performed for 20 min to obtain a self-cleaning and anti-adhesion rubber.

[0082] Example 10

[0083] A method for preparing self-cleaning and anti-adhesion rubber:

[0084] (1) A self-cleaning and anti-adhesive rubber, comprising the following components in parts by weight: 90 parts of natural rubber, 6 parts of nano zinc oxide, 1 part of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4010, 3 parts of paraffin, 55 parts of carbon black, 4 parts of aromatic oil, 1.5 parts of accelerator, 2 parts of sulfur, 10 parts of organic modified silicone, 4 parts of activated alumina, 4 parts of fluorine-containing polymer and 3 parts of lubricant (castor oil polyoxyethylene ether oleate).

[0085] The preparation method of the fluorine-containing polymer is:

[0086] A. Mix 1g of β-cyclodextrin and 10mL of 10wt.% potassium hydroxide solution, stir and react for 55min, then slowly drop 0.1mL of epichlorohydrin, heat and react after the addition is complete (temperature is 60°C, time is 8h, stirring speed is 300r / min), add acetone to precipitate after the reaction is complete, wash the precipitate with 50vol.% ethanol aqueous solution to obtain an intermediate product.

[0087] B. Disperse 10 mg of the intermediate product in 50 mL of water, add 4 g of a 0.5 wt.% potassium persulfate solution under a nitrogen atmosphere, and stir the reaction at 40°C for 30 min. Then, add 10 g of a 20 wt.% acrylamide solution and 200 mg of perfluoroalkenyloxybenzenesulfonyl chloride to the reaction system, and react at 60°C for 9 h. After the reaction, dry the mixture to obtain a fluorine-containing polymer.

[0088] (2) Preparation method

[0089] Same as Example 9.

[0090] Embodiment 11

[0091] A method for preparing self-cleaning and anti-adhesion rubber:

[0092] (1) A self-cleaning and anti-adhesive rubber, comprising the following components in parts by weight: 90 parts of natural rubber, 6 parts of nano zinc oxide, 1 part of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4010, 3 parts of paraffin, 55 parts of carbon black, 4 parts of aromatic oil, 1.5 parts of accelerator, 2 parts of sulfur, 10 parts of organic modified silicone, 3 parts of activated alumina, 6 parts of fluorine-containing polymer and 2 parts of lubricant (castor oil polyoxyethylene ether oleate).

[0093] The preparation method of the fluorine-containing polymer is:

[0094] A. Mix 1g of β-cyclodextrin and 8mL of 15wt.% potassium hydroxide solution, stir and react for 45min, then slowly drop 0.2mL of epichlorohydrin, heat and react after the addition is complete (temperature is 55°C, time is 8h, stirring speed is 300r / min), add acetone to precipitate after the reaction is complete, wash the precipitate with 50vol.% ethanol aqueous solution to obtain an intermediate product.

[0095] B. Disperse 10 mg of the intermediate product in 40 mL of water, add 4 g of a 0.5 wt.% potassium persulfate solution under a nitrogen atmosphere, and stir the reaction at 40°C for 30 min. Then, add 10 g of a 15 wt.% acrylamide solution and 200 mg of perfluoroalkenyloxybenzenesulfonyl chloride to the reaction system, and react at 62°C for 8 h. After the reaction, dry the mixture to obtain a fluorine-containing polymer.

[0096] (2) Preparation method

[0097] Same as Example 9.

[0098] Comparative Example 1

[0099] Same as Example 3, except that the organic modified silicone is replaced by an equal mass fraction of hydroxy-terminated polydimethylsiloxane.

[0100] Comparative Example 2

[0101] Same as Example 3, except that the organic modified silicone is replaced with an equal mass fraction of α,ω-dihydroxypolydimethylsiloxane.

[0102] Comparative Example 3

[0103] The same as Example 9, except that the activated alumina is replaced by an equal mass fraction of nano zinc oxide.

[0104] Comparative Example 4

[0105] Same as Example 9, except that castor oil polyoxyethylene ether oleate is replaced with oleic acid amide in equal parts by weight.

[0106] Comparative Example 5

[0107] Same as Example 9, except that the fluorine-containing polymer is replaced with PTFE 613A X (DuPont, USA) in equal parts by weight.

[0108] Comparative Example 6

[0109] Same as Example 9, except that the preparation method is as follows:

[0110] A. Add natural rubber, antioxidant RD, antioxidant 4010, paraffin, carbon black N330, aromatic oil, accelerator CZ, sulfur, stearic acid, nano zinc oxide, organic modified silicone, activated alumina, fluorine-containing polymer and lubricant into the internal mixer in sequence, then control the temperature of the internal mixer to about 60°C and the speed to 30r / min, mix for 5 minutes, and finally control the temperature of the internal mixer to 90°C, discharge the rubber and obtain the mixed rubber.

[0111] B. Thin pass: Move the mixed rubber to an open mixing mill and thinly pass it for kneading. Adjust the roller distance of the open mixing mill to 1mm, control the roller temperature to 52℃, and perform plasticizing. Thinly pass the mixed rubber for 5 times, and finally thicken the rubber by reducing the roller distance to 2.5mm and let it stand for 12 hours to obtain plasticized rubber.

[0112] C. Vulcanization: Put the plasticized rubber into a mold with a length, width and thickness of 100mm and 2mm, and then vulcanize it at a temperature of 145℃ and a pressure of 210kgf / cm 2 Under the conditions of , vulcanization was performed for 20 min to obtain a self-cleaning and anti-adhesion rubber.

[0113] Effect Example 1

[0114] The self-cleaning and anti-adhesion rubber prepared in the embodiments of the present invention and the comparative examples is made into a test piece with a length, width and thickness of 100 mm and 2 mm, and weighed h0 (unit: g). After weighing, 100 g of mud-water mixture h1 (unit: g) is evenly applied on each test piece, and then weighed h2 (unit: g). Then, the test piece coated with the mud-water mixture is adhered to the middle position of the belt surface (anti-adhesion test bench), and then the belt is allowed to run at a speed of 20 r / min for 5 minutes, and the test piece is removed and weighed h3 (unit: g). In this way, h2-h3 gives a value h4 (unit: g), which is the mass of the mud-water mixture that is not adhered to the test piece (the larger the value of h4, the more mud-water mixture is thrown away, which proves that its self-cleaning and anti-adhesion effects are better).

[0115] The anti-adhesion test workbench is a belt driven by a motor, the belt speed is 10-60r / min (adjustable), the belt is annular, the circumference is 1.2m, and the width is 200mm.

[0116] Preparation method of the mud-water mixture: 500 g of distilled water and 500 g of diatomaceous earth are mixed evenly to obtain a mud-water mixture.

[0117] Table 1 Rubber self-cleaning and anti-adhesion effects

[0118]

[0119]

[0120] It can be seen from Examples 3 to 7 in Table 1 that, within a certain range, as the amount of organic modified silicone increases, the self-cleaning property and anti-adhesion effect improve.

[0121] Effect Example 2

[0122] The self-cleaning and anti-adhesive rubber prepared in the examples of the present invention and the comparative examples was placed outdoors, and the contact angles of the rubber and water were measured after 6 months, 12 months and 24 months, respectively. The results are shown in Table 2.

[0123] Table 2 Rubber contamination

[0124]

[0125]

[0126] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A self-cleaning, anti-adhesion rubber, characterized in that: The invention comprises the following components in parts by weight: 90 to 110 parts of natural rubber, 4 to 6 parts of nano zinc oxide, 1 to 3 parts of stearic acid, 3 to 5 parts of antioxidant, 1 to 3 parts of paraffin wax, 45 to 55 parts of carbon black, 4 to 6 parts of aromatic oil, 1.0 to 1.5 parts of accelerator, 2 to 3 parts of sulfur, 2 to 10 parts of organic modified silicone, 3 to 4 parts of activated alumina, 4 to 6 parts of fluorine-containing polymer and 2 to 3 parts of lubricant; The organic modified silicone is Silicone aid 1330; The preparation method of the fluorine-containing polymer specifically comprises: A. Mix β-cyclodextrin and potassium hydroxide solution evenly and stir to react, then drop epichlorohydrin, and heat to react after the dropwise addition is completed, precipitate, and obtain an intermediate product; B. dispersing the intermediate product in water, adding potassium persulfate solution under a protective atmosphere, stirring for reaction, then sequentially adding acrylamide solution and perfluoroalkenyloxybenzenesulfonyl chloride, heating for reaction, and obtaining the fluorine-containing polymer; In step A, the concentration of the potassium hydroxide solution is 10-15wt.%; the mass / volume ratio of the β-cyclodextrin and the potassium hydroxide solution is 1g:8-10mL; the stirring reaction time is 45-55min; the mass / volume ratio of the β-cyclodextrin and epichlorohydrin is 1g:0.1-0.2mL; the heating reaction temperature is 55-60°C and the time is 8-9h; In step B, the mass / volume ratio of the intermediate product and water is 1 mg:4-5 mL; the concentration of the potassium persulfate solution is 0.5 wt.%; the mass ratio of the intermediate product and the potassium persulfate in the potassium persulfate solution is 1:2; the concentration of the acrylamide solution is 15-20 wt.%; the temperature of the heating reaction is 60-65° C., and the time is 8-10 hours.

2. The self-cleaning, anti-adhesion rubber according to claim 1, characterized in that: The lubricant is castor oil polyoxyethylene ether oleate.

3. The self-cleaning, anti-adhesion rubber according to claim 1, characterized in that: The particle size of the nano zinc oxide is 10-30 nm; the antioxidant is composed of antioxidant RD and antioxidant 4010 in a mass ratio of 1:

1.

4. The self-cleaning, anti-adhesion rubber according to claim 1, characterized in that: The carbon black is carbon black N330; and the accelerator is accelerator CZ.

5. A method for preparing the self-cleaning and anti-adhesion rubber according to any one of claims 1 to 4, characterized in that: The following steps are involved: Weigh each raw material by mass, mix natural rubber, stearic acid, antioxidant, paraffin, carbon black, aromatic oil, accelerator and sulfur evenly and knead them once, then add nano zinc oxide, organic modified silicone, activated alumina, fluorine-containing polymer and lubricant for secondary kneading, and finally thin pass and vulcanize to obtain the self-cleaning and anti-adhesion rubber.